Crisis, democratización y reproducción: el potencial revolucionario de un arte sin aura - Milla, Saraí (2025)
The aim of this paper is to analyze Walter Benjamin’s proposal on the revolutionary potential of art with the change in its conditions of production and reception. To this end, we will study the social and political impact of the emergence of art without aura, which challenges the authority of the aesthetic object and establishes new connections with its audience. We will examine the risks brought about by the democratization of art to understand how the critical power of post-aura art opens up a collective space for questioning and transforming established structures.